Retroperitoneal Cystic Lymphangioma: A Diagnostic and Surgical Challenge. (28th February 2013) - Gümüştaş, Oguzhan Güven; Sanal, Murat; Güner, Osman; Tümay, Volkan
Abstract : A lymphangioma is a benign proliferation of lymph vessels, producing fluid-filled cysts that result from a blockage of the lymphatic system. The incidence of abdominal lymphangiomas is unknown; however they account for from 3% to 9.2% of all pediatric lymphangiomas, with retroperitoneal lymphangioma representing less than 1% of abdominal lymphangiomas. Due to rarity, preoperative diagnosis is often difficult.